An Apparent Lack of Epidemiologic Association between Hepatitis C Virus Knowledge and the Prevalence of Hepatitis C Infection in a National Survey in Egypt - Chemaitelly, Hiam; Abu-Raddad, Laith J.; Miller, F. DeWolfe (PLOS ONE, 2013)
Background Egypt has by far the largest hepatitis C virus (HCV) prevalence in the world with 14.7% of the population being antibody positive for HCV. The aim of this study was to examine the association between knowledge of HCV and HCV antibody positivity among the Egyptian population. Methods We characterized different measures of HCV knowledge and examined their associations with HCV prevalence, by analyzing a nationally representative database using standard epidemiologic methods. The database, the 2008 Egyptian Demographic and Health Survey, included demographic, health, and HCV biomarker information for a sample of over 12,000 individuals. Results Basic knowledge of HCV was found to be high, but multiple gaps were identified in the specific knowledge of HCV and its modes of transmission. There was no statistically significant difference in HCV prevalence between those who have heard of HCV infection and those who have not (14.4% vs. 15.9%, p>.05). Similar results were found for the other HCV knowledge measures including those specific to HCV modes of transmission and to the sources of information for HCV awareness. Logistic regression analyses did not demonstrate an association between HCV knowledge and HCV prevalence. Conclusions Our results do not provide support for an effect of awareness on reducing the risk of HCV infection in Egypt. Public health messages directed at the lay public may not provide sufficient empowerment for individuals to avoid HCV infection, and should be complemented with prevention programs to promote and strengthen infection control in the settings of exposure, particularly in health care facilities.